Terapi kalsitriol intravena pada hiperparati roidisme sekunder penderita gaga! ginjal kronik yang menjalani hemodialisis rutin di RSUP DR. Sardjito Yogyakarta - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1999)
ABSTRACT Background: Secondary hyperparathyroidism is common in patients with chronic renal failure. Secondary hyperparathyroidism with vitamin D deficiency may increase renal osteodystrophy. Objective: To determine the blood intact parathormone (iPTH) level in routinely hemodialyzed patients with secondary hyperparathyroidism undertaking calcitriol intravenous therapy once in two weeks. Methods: a double blind randomized clinical trial had been done in 32 chronic renal failure patients from 41 secondary hyperparathyroidism who underwent regular hemodialysis in Dr. Sardjito Hospital Yogyakarta. All patients received intravenous calcitriol 11.1.g or placebo twice a week after dialysis for 2 weeks. The proportion of the decrease of iPTH level at least 30%